(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: An association between thyroid dysfunction and dyslipidemia prevails. Levels of total cholesterol, low density lipoprotein cholesterol, triglycerides tend to increase as thyroid function declines. Objective: To find out the pattern of dyslipidemia in hypothyroid patients. Methods: Sixty cases were selected as a sample of convenience in this cross sectional study from in-patienl depa1tment of Medicine and Endocrinology, BSMMU. Meticulous history taking and thorough clinical examinations were done. Report of lipid profile and thyroid function tests were recorded from patients file. All the information’s were recorded in a pre-designed sttuctured questionnaire. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS. Results: Among the 60 cases, 43 (72%) were female; 17(28%) were male. Age range was 24-59 years with a mean age of 38.80 (± I 0.35) years. Majority 38(65%) were housewife, followed by service holder 11(18.33%), 08(13.3%) were business men and 02(3.3%) had other occupations. Majority 42(70%) patients were taking thyroxin. Mean Total cholesterol (TC), LDL cholesterol, Triglyceride (TG) and HDL were 222.20(±42.25); 138.63(±31.51); 243.36(±83.13) and 37.30(±5.12) respectably. Conclusion: All hypothyroid subjects had dyslipidemia. The present study indicated that hypothyroidism was associated with an abnormal lipid profile, especially with respect to the levels of total cholesterol and triglyceride.